Understanding diabetes and its complications through the lens of Drosophila. - Bevinakoppamath, S.; Srinivas, A.; Chandan Gowda Umesha; Prashant, A.; Singh, A.; Rao, V.K. (Experimental and molecular pathology, 2026)
A significant gap exists between preclinical findings in animal models and their translation to diabetes therapeutics. Although several generic drugs are currently available, an effective and precise control of glycemia is challenging, and side effects due to both hyperglycemia and drugs are common. This is partly due to our incomplete understanding of disease mechanisms. It is now appreciated that, due to its simplicity and well-conserved genetic pathways, Drosophila disease modeling is an excellent choice for studying diabetes and its complications. Here, we review knowledge about conserved glucose sensing mechanisms, energy homeostasis pathways, and diabetes modeling in Drosophila. We discuss how hyperglycemia-induced metabolic deregulations cause diabetic complications. Further through the lens of Drosophila, we highlight molecular mechanisms underlying vascular and emerging diabetic complications, including neurodegeneration and cancer. We conclude with the thought that diabetes modeling in Drosophila could prove beneficial in large-scale screening of drugs for diabetes and its complications.